Effectiveness of the human placenta hydrolyzate in the treatment of menopausal symptoms in women in the menopausal transition - I V Kuznetsova; A V Gilels; Yu B Uspenskaya; N S Suleymanova (IP Berlin A.V., 2013)
Contraindications to hormone therapy in peri - and postmenopausal periods, as well as giving up hormones determine the relevance of the search for alternative methods of relief of menopausal disorders. Thus we conducted a comparative study of the effectiveness of the hydrolyzate of human placenta and phytoestrogens in women of peri- and postmenopausal period with the presence of symptoms caused by estrogen deficiency. Evaluation of initial severity of menopausal disorders and the effectiveness of therapy was carried out by the Cupperman index. The study had a positive effect, in response to a human placenta hydrolyzate therapy and using phytoestrogens. But the decline of Cupperman index in the group of women treated with hydrolyzate of human placenta was significantly greater, and continued to grow in the period after treatment , whereas the decrease in the Cupperman index while taking phytoestrogens was observed during the first two months of receiving stabilizing for subsequent treatment. Application of human placenta hydrolyzate had a positive effect on blood pressure in patients with hypertension and improved blood lipid. Thus, the use of the hydrolyzate of human placenta can serve as an alternative hormonal therapy in women of peri - and post-menopausal age.